Factors associated with the delay in seeking first antenatal care service among pregnant women at Katutura state hospital, Khomas region - Maano, Nghitanwa Emma; Tuwilika. N., Shanyengange (International Journal of Medicine, 2017)
The purpose of this study was to identify the factors associated with the delay in seeking first antenatal care (ANC) service among pregnant women at Katutura state hospital, Khomas region. A qualitative, explorative and descriptive design was used to gain the data from pregnant women started first antenatal care later than twelve weeks of gestation.Data was collected through in-depth interview among pregnant women during their first visit at Katutura state hospital antenatal clinic, Khomas region. The data analysis was done in line with thematic analysis and themes and sub-themes were identified.The study findings concluded that most pregnant women attend their first ANC later than twelve weeks gestation because of work commitment, long distance to health facilities, and lack of knowledge about the important of starting ANC in first trimester of pregnancy.The study recommends the establishment and implementation of a community based health education programs about the antenatal care services in order to create awareness and knowledge in the community about the importance of starting antenatal care services during the first trimester of pregnancy.